Aggressive script rehearsal in adult offenders: Relationships with emotion regulation difficulties and aggressive behavior. Issue 1 (19th October 2021) - Hosie, Julia; Dunne, Ashley Lauren; Meyer, Denny; Daffern, Michael
Abstract: This study explored relationships between self‐reported emotion regulation difficulties, frequency of aggressive script rehearsal and aggressive behavior in 129 adult male inmates. Significant moderate positive correlations were found between the frequency of aggressive script rehearsal and (1) emotion regulation difficulties overall, as well as the following dimensions, (2) difficulties controlling impulses when experiencing negative emotions, and (3) confidence in the effectiveness of emotion regulation strategies. Significant weak positive correlations were found between the frequency of aggressive script rehearsal and two emotion regulation difficulty dimensions, (1) a lack of understanding of emotional responses, and (2) difficulties in dealing with goal directed behavior when experiencing uncomfortable emotions. No significant correlations were found between aggressive behavior and emotion regulation difficulties, except for a weak positive correlation between aggressive behavior and difficulties controlling impulses when experiencing negative emotions. Multivariate analyses were used to assess whether the frequency of aggressive script rehearsal moderated the effect of emotion regulation difficulties on aggressive behaviour. Significant improvement in the prediction of aggression resulted from consideration of the interaction between (1) aggressive script rehearsal and difficulties in emotional clarity, and (2) aggressive script rehearsal and awareness of emotional experience, even after accounting for the influence of age and attitudes toward violence. In conclusion, the results suggest that the rehearsal of aggressive scripts may function to regulate emotion, particularly amongst people who are inattentive to their emotions or who have difficulty understanding their emotional experiences.